An Evaluation of the Efficacy of Different Gingival Retraction Materials on the Gingival Tissue Displacement (A Comparative In Vivo Study) - Zainab M Dawood; Manhal A Majeed (College of Dentistry/ University of Baghdad, 2015)
Background: An accurate adaptation of the crown to the finish line is essential to minimize cement dissolution and to preserve periodontium in fixed partial denture cases. An accurate adaptation of crown is possible only when preparation details are captured adequately in the impression and transferred to cast. For these reasons, gingival displacement is necessary to capture subgingival preparation details.The aim of the present study is to measure in vivo the horizontal displacement of the gingival sulcus obtained by using three new cordless retraction materials (Magic Foam Cord®, Racegel and Astringent Retraction Paste) in comparison to medicated retraction cord. Materials and method: Thirty-two patients requiring porcelain fused to metal fixed partial denture for replacement of a missing maxillary posterior tooth (either one of thepremolars or the first molar). The patients are randomly divided into four groups of eight patients each according to the type of gingival retraction material used as follows: Group I: Medicated retraction cord (racemic epinephrine hydrochloride 0.3 ± 0.2 mg per inch of cord, #00), Group II: Magic Foam Cord® (expanding polyvinyl siloxane), Group III: Racegel (25% aluminum chloride gel) and Group IV: Astringent Retraction Paste (15% aluminum chloride paste). Three depth orientation grooves were prepared in the buccal and palatal surfaces of a maxillary premolar parallel with the long axis of the tooth, extending from the middle third to the gingival third with the level of the free gingiva using a flat-ended diamond fissure bur. Impression of the gingival sulcus was then made using monophase polyether impression material (Impregum™ Penta™ Soft, 3M ESPE, Germany), before and after gingival retraction with either of the aforementioned gingival retraction materials. The sulcus width, before and after gingival retraction was measured on the master cast (in µm), after its sectioning longitudinally bucco-palatally at the middle of the prepared grooves using a rotary diamond disc. The measurement carried out by using digital microscope (Dino-Lite)at a magnification of 230X. The horizontal gingival displacement (the distance from the end of each prepared groove to the crest of the gingiva) measured by subtracting the gingival sulcus width after retraction from that before retraction. Results: The findings of the present study showed that the highest mean of horizontal gingival displacement is recorded by Group IV (Astringent Retraction Paste) (250.7900 µm), whereas the lowest mean of horizontal gingival displacement is recorded by Group III (Racegel) (78.0988 µm). One-way ANOVA test showed statistically highly significant differences among groups (p< 0.01). Least Significant Difference test (LSD test) was also used to make multiple comparisons among groups and revealed a statistically highly significant difference between each two groups (p< 0.01). Conclusion: The two new gingival retraction pastes (Astringent Retraction Paste and Magic Foam Cord®) could be used for gingival retraction as alternatives to medicated retraction cord. They offer advantages of simplified placement technique and shorter application time with greater gingival retraction. Meanwhile, the use of Racegel alone is not recommended for gingival retraction since it provides the least gingival displacement.